2012
DOI: 10.1063/1.4719972
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of magnetoelectric effect by combining different interfacial coupling mechanisms

Abstract: First-principles calculations were used to investigate the interfacial electronic structure and magnetoelectric effect in the Fe/PbTiO3 heterointerface. We demonstrate that the large magnetoelectric effect in this system is determined by the combination of different magnetoelectric coupling mechanisms, i.e., the conjunction of interface bonding mechanism and the electrostatic screening of the spin-polarized carriers. The change of induced magnetic moments on interfacial Ti atoms is due to the variation of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…PbTiO 3 has a larger out-of-plane polarization and a smaller ferroelectric critical size than common ferroic materials such as BaTiO 3 and BiFeO 3 49 – 51 . In addition, the MEC of PbTiO 3 -based heterostructures is larger than that of BaTiO 3 system 52 . Therefore, PbTiO 3 is selected as the ferroelectric layer in the present study.…”
Section: Resultsmentioning
confidence: 91%
“…PbTiO 3 has a larger out-of-plane polarization and a smaller ferroelectric critical size than common ferroic materials such as BaTiO 3 and BiFeO 3 49 – 51 . In addition, the MEC of PbTiO 3 -based heterostructures is larger than that of BaTiO 3 system 52 . Therefore, PbTiO 3 is selected as the ferroelectric layer in the present study.…”
Section: Resultsmentioning
confidence: 91%
“…For instance, density functional theory (DFT) calculations for Fe/BaTiO 3 (001) show a large surface magnetoelectric response whose origin is largely attributed to changes in the chemical bonding at the interface, i.e., to modulations in the Ti 3d, Fe 3d and O 2p orbital overlap upon reversal of the ferroelectric polarization direction due to the displacement of the Ti atoms, which additionally become magnetically polarised. [105][106][107][108][109][110] The latter effect has been observed experimentally in Fe/BaTiO 3 (001) by so X-ray resonant magnetic scattering, 111 which shows that the Ti cations become ferromagnetic by proximity with the Fe lm, turning the interface region of BaTiO 3 both ferroelectric and ferromagnetic, i.e., multiferroic, at room temperature. The modulation of the charge carrier density at the interface can also modify strongly the surface magnetic anisotropy of a ferromagnetic material via spin-orbit coupling through a change in the relative electron occupancy of the different d orbitals.…”
Section: Proximity Effects and Artificial Multiferroicsmentioning
confidence: 77%
“…On the other hand, the interface bonding causes charge redistribution between the majority and minority spins for Ti 3d and O 2p states, giving rise to induced magnetic moments on the interfacial Ti and O atoms of about À0.04 and 0.04, respectively. Previous first-principles calculations 40 have demonstrated that large magnetoelectric coupling occurs in the Fe/PbTiO 3 heterointerface due to combination of different magnetoelectric coupling mechanisms when the ferroelectric polarization of PbTiO 3 reverses. Second, it is clear that the occupancies of Ti d xz þ d yz states are increased observably as the TiO 2 atomic plane moves from the interfacial to the central layer while the occupancy of Ti d xy states in the central TiO 2 layer is much less than that in the TiO 2 monolayers with l ¼ À4 and À2.…”
Section: Formation Of the Hh 180 Domain Wallmentioning
confidence: 98%
“…The work of separation between Fe and PbTiO 3 slabs is determined to be 2.62 J/m 2 , which is more than four times larger than the Fe/BaTiO 3 system. 40 domain wall. As we see later, the screening electronic charges are situated on the Ti 3d orbitals, so it is more meaningful to take into account the planar-averaged electrostatic potentials of the TiO 2 atomic planes.…”
Section: Formation Of the Hh 180 Domain Wallmentioning
confidence: 99%
See 1 more Smart Citation